ANALISIS MANAJEMEN RISIKO SISTEM INFORMASI PERPUSTAKAAN UNIVERSITAS LAMPUNG MENGGUNAKAN METODE NIST SP 800-30 - Danis Sela Valena; rizky Prabowo; anie Rose irawati; aristoteles aristoteles (Universitas Lampung, 2019)
The rapid growth of implementing library information system causing a thrreatening risk. The main cause of the risk is from librarian it self that cannot evaluate which of the factor is a potential threat. This research intend to analyze the risk management of library information system in library of Lampung University, this research using NIST SP 800-30 method. This library information system risk management held for anticipating the source of threat by the following step risk assesment, risk mitigation, and risk evaluation. The result of this risk management is, late book returning, book disspearance, no backup data sejarah of damaged book, theres no matching between data in system and stock in library, data falsisication in borrowing book, redundant data, expired KTM, and lack of understanding when uploading skripsi by scholar. The from risk assesment for late book returning is high risk, to reduce and eliminate the impact of risk library of Lampung University do risk mitigation with early warning. The factor that influencing library information system Lampung University risk assesment is human resource that having and ability in information technology for convenience support to risk all risk in every circumstances